Jewish and Christian Approaches to the Psalms: Conflict and Convergence. Edited by Susan Gillingham - Firth, David G. (The journal of theological studies, 2014)
This helpful volume collects the papers given at a conference on the interpretation of Psalms at Worcester College, Oxford, in 2010, though the papers have been revised for publication. After an introduction by Susan Gillingham which sets the context for the conference and briefly outlines each of the papers, the book is divided into three unequal sections. The first part, comprising roughly half the book, considers ‘Jewish and Christian Responses to the Psalms’. Part II then looks at ‘Reading the Psalter’, whilst the final part considers ‘Past Contexts and Future Perspectives’. It would probably be fair to say that the book’s title only really addresses the content of Part I, as the issue of Jewish and Christian interpretation plays only a relatively minor role in Parts II and III.